Double-balloon catheter compared with single-balloon catheter for induction of labor with a scarred uterus. (December 2019) - Xing, Yanping; Li, Na; Ji, Qiumei; Hong, Lingling; Wang, Xuezhen; Xing, Baoheng
Abstract: Background: In obstetrics, labor induction is a common procedure. It has been proved that both single balloon catheters (Foley's catheter) and double balloon catheters (Cook cervical ripening balloon) are effective and relatively safe in cervical ripening and labor induction. This research aimed to compare the efficacy of single and double balloon catheter in the induction of labor with scarred uterus. Methods: 120 pregnant women who had prior cesarean delivery participated in this research and were randomized into single-balloon catheter group (n = 60) and double-balloon catheter group (n = 60). The cervical ripening effect, security, and influence to the process of childbirth were analyzed in each group. Results: The validity of cervical ripening in single balloon group was better than double balloon group. Double balloon catheters increased the time between insertion and expulsion of the catheter and decreased spontaneous catheter expulsion rate. All the neonatal outcomes in these two groups were comparable. Conclusion: Based on our data, the two different catheters both have their pros and cons in the labor induction of pregnant women with scarred uterus. The appropriate catheter used based on specific circumstance will improve the quality of labor induction.